Efficient Synthesis of 2‐Methylfuran from Bio‐Derived Furfural over Supported Copper Catalyst: The Synergistic Effect of CuOx and Cu. Issue 31 (2nd November 2017) - Gong, Wanbing; Chen, Chun; Zhang, Haimin; Wang, Guozhong; Zhao, Huijun
Abstract: Transforming biomass into value‐added chemicals will reduce our reliance to fossil resources. This work reports the development of an activated carbon (AC) supported Cu‐based catalyst (Cu/AC) capable of efficiently convert bio‐derived furfural (FAL) into 2‐methylfuran (2‐MF), a valuable chemical and bio‐fuel. The Cu/AC catalyst was synthesized by a facile ultrasound‐assisted impregnation method with the aid of the reduction property of active carbon. The effect of synthetic conditions was investigated. It was found that the best performed catalyst (Cu/AC‐400/2) can be obtained from 2 h calcination at 400 °C. With Cu/AC‐400/2 as the catalyst, an almost 100% yield of 2‐MF can be obtained within 4 h under 170 °C reaction temperature and 3 MPa H2 pressure. Experimental evidence suggested that FAL was catalytically converted into 2‐MF via the formation of furfuryl alcohol (FOL) intermediate. Extensive characterization results indicated that the superior catalytic performance of Cu/AC‐400/2 catalyst could be attributed to the uniform sized and well dispersed Cu nanoparticles (NPs) with optimal proportions of Cu 2+, Cu 0 and Cu + embedded on large surface area porous active carbon. Cycling test proved the synthesized catalyst could be reutilized during successive catalytic cycles because of Cu NPs distributed uniformly on the AC surface and the weak interaction between copper and support. Abstract : The copper catalyst was synthesized by a facile ultrasound‐assisted impregnation method using the reducing property of activated carbon, which acted as the reducing agent, dispersant, stabilizer as well as the support. This material, Cu/AC‐400/2, displayed showed excellent catalytic performance for converting furfural to 2‐methylfuran in liquid‐phase. An almost 100% yield of 2‐methylfuran can be obtained within 4 h under 170 °C reaction temperature and 3 MPa H2 pressure.